2005
DOI: 10.1159/000082783
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perindopril on Cerebral and Renal Perfusion on Normotensives in Mild Early Ischaemic Stroke: A Randomized Controlled Trial

Abstract: Background and Purpose: Blood pressure reduction is central to secondary prevention after stroke, but the optimal time to start therapy is unknown. Cerebral autoregulation is impaired early after ischaemic insult, and any changes in systemic blood pressure may be reflected in cerebral perfusion. However, early initiation in hospital may better assure continued long-term treatment. We have investigated the effect of the angiotensin-converting enzyme inhibitor perindopril on blood pressure, global and focal cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Small studies looking at surrogate markers of cerebral blood flow such as SPECT have indicated that neither perindopril nor losartan lower cerebral blood flow when given within 2–7 days of stroke onset [370]. Several ongoing trials are examining whether BP should be lowered after acute stroke, and whether antihypertensive therapy should be continued or stopped in the first few days after stroke [371, 372].…”
Section: General Stroke Treatmentmentioning
confidence: 99%
“…Small studies looking at surrogate markers of cerebral blood flow such as SPECT have indicated that neither perindopril nor losartan lower cerebral blood flow when given within 2–7 days of stroke onset [370]. Several ongoing trials are examining whether BP should be lowered after acute stroke, and whether antihypertensive therapy should be continued or stopped in the first few days after stroke [371, 372].…”
Section: General Stroke Treatmentmentioning
confidence: 99%
“…Several drug classes were studied including angiotensin-converting enzyme inhibitors (ACE-I), angiotensin receptor antagonists (ARA), calcium channel blockers (CCBs), diuretics and nitrates [13,14,15,16,17,18,19]. Overall, no drug class showed a decrease in CBF, and some studies of CCBs (albeit non-randomised) suggested an increase [12].…”
Section: Effects Of Antihypertensive Agents On Cbfmentioning
confidence: 99%
“…Three ACE-I (captopril, lisinopril, perindopril) have been assessed across five randomised trials involving a total of 221 patients [14, 15, 18, 20, 21]. In one study, perindopril lowered BP without having detrimental effects on CBF [15].…”
Section: Effects Of Antihypertensive Agents On Outcomementioning
confidence: 99%
“…The normalization of blood pressure has been shown to mostly occur over a period of 4–5 days [1, 4] and we have only studied the first 48 h after stroke. It is likely, however, that therapeutic manipulation of blood pressure would begin during these first 48 h, so we chose to focus on this period, though we note that Nazir et al[ 20] studied blood pressure lowering with perindopril in a subgroup recruited up to 8 days after stroke. Our study did not include a protocol for the use of antihypertensive therapy because we felt there was insufficient evidence to guide the development of a protocol.…”
Section: Discussionmentioning
confidence: 99%